Atlas of ACE spectra of clouds and aerosols. (December 2022) - Lecours, Michael J.; Bernath, Peter F; Sorensen, Jason J; Boone, Chris D; Johnson, Ryan M; LaBelle, Keith
Highlights: Atmospheric chemistry Experiment, ACE. Characteristic IR solar absorption spectroscopy of clouds and aerosol particles. Cloud and aerosol particle spectral analysis and modeling. Satellite remote sensing by Fourier transform infrared spectroscopy. Abstract: Clouds and aerosols play a vital role in the Earth's climate. Detecting polar mesospheric clouds, polar stratospheric clouds and aerosols is useful for monitoring climate change and atmospheric chemistry. ACE (Atmospheric Chemistry Experiment) satellite data are used to provide an infrared spectral atlas of polar mesospheric clouds, three types of polar stratospheric clouds (nitric acid trihydrate, sulfuric/nitric acid ternary solutions, and ice), cirrus clouds, stratospheric smoke from fires and sulfate aerosols. Most of the example spectra have been modeled using the appropriate optical constants and the calculated extinction of sunlight by the particles.